Analysis of Research Publication on Logistics at the Time of COVID-19: A Scientometric Study - Thangaraju, Pugazhenthan; Verma, Ku Krishna; Velmurugan, Hemasri; Chandu, Himanshu N.; Chakrabarti, Tulika; Chakrabarti, Prasun; Venkatesan, Sajitha (Coronaviruses, 2023)
Coronaviruses have a wide range of health, mobility, and economic consequences. The Coronavirus pandemic is an unprecedented incident that has drawn the attention of the general public to supply chain management. It caused severe interruptions between 2020 and 2022. Despite the importance and size of the impact of coronaviruses on research performance across time, the literature on comprehensive coronavirus-related research performance is limited. This study aimed at a scientometric evaluation of bibliographic facts associated with the supply chain during the pandemic, and data related to it was extracted from PubMed between January 2020 and December 2022. The purpose of this research is to examine scientometric methods such as frequency distribution, percentage analysis, relative growth rate, doubling time, and degree of collaboration. We have obtained a total of 116 publications during this study period, and a maximum of 26 (22.4%) contributions were made in the months of May to August 2021. The relative growth rate is declining, and the doubling time is increasing between May to August 2021. Scientifically analysing and comprehending bibliographic facts associated with the supply chain during the COVID-19 pandemic as widely as possible can also assist society in being better prepared for future pandemic breakouts, ultimately supporting informed decision-making in light of societal values. The authors highly advocate the recent COVID-19 epidemic as a call for greater collaborative, worldwide research.
Keywords: supply chain